Types of Acute Lung Injury and Fat Embolism - Ye. A. Kameneva; S. S. Koval; Ye. V Grigoryev; A. S. Razumov; O. N. Yegorova; T. A. Pavlova (Общая реаниматология, 2008)
Objective: to enhance the efficiency of diagnosing acute lung injury (ALI) and fat embolism (FE). Subjects and methods: Forty-seven patients with severe concomitant trauma (SCT), divided into three groups by the severity of shock and injury, were examined. The parameters of the scales rating ALI severity, lipid metabolism, hemostatic system, and hemodynamic monitoring were analyzed. Results. Three types of acute lung injury were identified in FE depending on clinical laboratory parameters: the patients having a shockogenicity index of less than 14 scores had significantly activated coagulation hemostasis and suppressed fibrinolytic system. Those with a shockogenicity index of 15 to 22 scores developed hemostatic disorders as activated coagulation hemostasis throughout the study and considerably activated fibrinolytic system, the levels of atherogenic very low density lipoproteins (LVDL) and triglycerides increased. The patients with a shockogenicity index of more than 23 scores developed hemostatic disorders, such as pronounced activation of the blood coagulation system and suppression of the fibrinolytic system. The manifestation of ALI increased with the elevated concentrations of LVDL and triglycerides, hypercoagulation by hemo-viscosimetric parameters and reduced platelets, lower oxygenation index, and decreased oxygen consumption. Conclusion. A scheme of development of the types of ALI and FE has been proposed. Key words: severe injury, acute lung injury, fat embolism, types of diagnosis.